Factor Contributing To Organizational Citizenship Behavior - Andryansah, Galang; Suwarno, Hadi; Afrizal, Very (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study explores the interplay between organizational culture and servant leadership and their collective impact on organizational citizenship behavior (OCB). The purpose of this research is to ascertain and analyze how organizational culture and servant leadership affect organizational citizenship behavior at PT. Surya Furniture Indonesia. There is a quantitative study type that is conducted. Furthermore, using associative techniques to determine the ways in which Organizational Culture and Servant Leadership impact Organizational Citizenship Behavior. There were seventy-three subjects in this investigation, and nonprobability sampling with saturated sample techniques was used to identify the samples. In line with the respondent company, PT. Surya Furniture Indonesia. Instruments employ a Likert scale. To find out how much organizational culture and servant leadership influence organizational citizenship behavior, a multiple regression analysis was carried out with SPSS 26.0. Organizational Culture was found to have a substantial beneficial impact on Organizational Citizenship Behavior (p=0.032, t=2,190). Servant leadership significantly improves organizational citizenship behavior (p-value = 0.000, t-count = 27688). Organizational culture and servant leadership both demonstrated a strong positive impact on organizational citizenship behavior, with a p-value of 0.000 and an f-count of 378,058. The findings suggest that a positive organizational culture significantly enhances the effectiveness of servant leadership practices, which in turn, fosters higher levels of OCB among employees.